Analisis Psikologi Strukturalisme Wundt terhadap Tabel Refleksi Siswa dalam Buku Paket Wonderful Insight English Kelas VII oleh Erlangga Tahun 2023 - Faradilla Zahratun Nisa; Arbaiyah Yusuf; Fika Hawi Lestari; Fauzi Novandiansyah (Universitas Palangka Raya, 2025)
This study aims to analyze the reflection table in the book Wonderful Insight English class VII published by Erlangga in 2023 based on the perspective of Wilhelm Wundt's structuralism psychology. The reflection table contains five main statements, namely Now I know about, I wonder about, It is confirmed that, My misconception so far was that, and I have learnt about, which are designed to help students evaluate their learning experiences. The research uses a descriptive qualitative method with a document analysis approach, and utilizes the concept of introspection and elements of consciousness in Wundt's theory of structuralism. The results of the analysis showed that each statement of reflection represented a different stage of consciousness. Now I know about marking the emergence of new knowledge, I wonder about reflecting curiosity and further thinking process, It is confirmed that it shows the strengthening of the understanding that has been had, My misconception so far was that it reveals awareness of misconceptions, while I have learnt about affirming the final result of learning. These findings confirm that the reflection table in the book has facilitated the process of student introspection, while strengthening learning awareness in line with the principles of structuralism psychology Wilhelm Wundt. Thus, reflection is an important instrument in building students' cognitive awareness in 21st century learning.